Short and Medium-term Efficacy and Safety of “Sinotech+” (Uzbekistan) Stent in Primary Stenting for Patients with Acute Coronary Syndrome with ST-Segment Elevation (CARDIOLOGY OF UZBEKISTAN, 2025)
Aim. To evaluate the efficacy and safety of the Uzbekistan-manufactured “Sinotech+” stent during primary percutaneous coronary intervention (pPCI) in patients presenting with ST-elevation acute coronary syndrome (STEMI). Materials and methods. The study was conducted at the X-ray Endovascular Treatment Department of Cardiovascular Diseases at the RSSPMCC. Between January and June 2025, all 31 patients diagnosed with STEMI underwent pPCI procedures. "Sinotech+" stents were implanted in 17 patients (54.8%), while "Resolute Integrity" stents were implanted in 14 patients (45.2%). Patients who received "Sinotech+" stent implantation were analyzed. Results. Coronary lesion distribution was as follows: single-vessel disease in 5 patients (29.4%), two- vessel disease in 7 patients (41.2%), and multi-vessel disease in 5 patients (29.4%). Pre-procedural coronary flow assessment using the TIMI (Thrombolysis in Myocardial Infarction) perfusion scale revealed TIMI-0 flow in 9 patients (53%) and TIMI-1 flow in 8 patients (47%). Following pPCI, TIMI-3 flow was achieved in 14 patients (82.4%), while TIMI-2 flow was achieved in the remaining 3 patients (17.6%). These results demonstrated 100% technical success (stent deployment and vessel opening) and 82.4% angiographic success (achieving TIMI-3 flow), indicating high clinical efficacy of primary PCI using “Sinotech+” stents. Conclusion. The Uzbekistan-manufactured “Sinotech+” stent demonstrated high efficacy and safety in patients presenting with STEMI. No complications (thrombosis, restenosis, recurrent myocardial infarction, repeat revascularization) were observed during clinical follow-up.